ISLAMIC RELIGIOUS EDUCATION STRATEGIES IN PREVENTING ETHICAL ANOMALIES IN TAKHASSUS AL-QUR'AN VOCATIONAL SCHOOL IN WONOSOBO - Khowi Uswatun Hasanah; Muhammad Yusuf Amin Nugroho; Aryadi Nursantoso (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
Ethical anomalies among students are a serious issue that requires strategic handling through education. This study aims to describe the Islamic Religious Education (PAI) strategy in preventing ethical anomalies at SMK Takhassus Al-Qur'an Wonosobo, identify the strategies implemented by the school, and analyze the supporting and inhibiting factors. The method used is descriptive qualitative research with data collection techniques through observation, in-depth interviews, and documentation. Research informants included the principal, PAI teachers, Guidance and Counseling (BK) teachers, and students. The results show that SMK Takhassus Al-Qur'an Wonosobo applies four main PAI strategies, namely: (1) teacher role model strategy; (2) habituation strategy through religious activities such as reciting istighosah, congregational Dhuhur prayer, and the habituation of smiling, greeting, and saluting; (3) Islamic values ​​strategy through intracurricular and extracurricular activities; and (4) strategy for handling and monitoring deviant behavior through a points and remission system. Supporting factors include a conducive Islamic boarding school environment, commitment from all teaching staff, and a program to preserve the uniqueness of the Quran. Inhibiting factors include the uncontrolled influence of digital media and the gap between moral understanding and daily practice. This study concludes that an integrated approach between Islamic Religious Education (PAI) learning in the classroom and religious practices in the boarding school environment has proven effective in preventing ethical anomalies among students.